ГДЗ до підручника «Алгебра» А.Г. Мерзляка. 7 клас

441. 1) 2х(а + b) + у(а + b) = (a + b)(2x + у);

2) (а - 4) - b(а - 4) = (а - 4)(1 - b);

3) 5а(m - n) + 7b(m - n) = (m - n)(5а + 7b);

4) 6х(4х + 1) - 11(4х + 1) = (4х + 1)(6х - 11);

5) а(с - d) + b(d - с) = а(с - d) - b(c - d) = (c - d)(a - b);

6) x(x - 6) - 10(6 - x) = x(x - 6) + 10(x - 6) = (x - 6)(x + 10);

7) b(b - 20) + (20 - b) = b(b - 20) - (b - 20) = (b - 20)(b - 1);

8) 6a(a - 3b) - 13b(3b - a) = 6a(a - 3b) + 13b(a - 3b) = (a - 3b)(6a + 13b);

9) (m - 9)2 - 3(m - 9) = (m - 9)(m - 9 - 3) = (m - 9)(m - 12);

10) a(a + 5)2 + (a + 5) = (a + 5)(a(a + 5) + 1) = (a + 5)(a2 + 5a + 1);

11) (m2 - 3) - n(m2 - 3)2 = (m2 - 3) • (1 - n • (m2 - 3)) = (m2 - 3)(1 - nm2 + 3n);

12) 8c(p - 12) + 7d(p - 12)2 = (p - 12) • (8c + 7d(p - 12)) = (p - 12)(8c + 7dp - 84d).

442. 1) c(x - 3) - d(x - 3) = (x - 3)(c - d);

2) m(p - k) - (p - k) = (p - k)(m - 1);

3) m(x - y) - n(y - x) = m(x - y) + n(x - y) = (x - y)(m + n);

4) x(2 - x) + 4(x - 2) = x(2 - x) - 4(2 - x) = (2 - x)(x - 4);

5) 4x(2x - y) - 5y(y - 2x) = 4x(2x - y) + 5y(2x - y) = (2x - y)(4x + 5y);

6) (у + 1)2 - 4y(y + 1) = (y + 1)(y + 1 - 4y) = (y + 1)(1 - 3y);

7) 10(a2 - 5) + (a2 - 5)2 = (a2 - 5)(10 + a2 - 5) = (a2 - 5)(5 + a2);

8) (a - 2)2 - 6(a - 2) = (a - 2)(a - 2 - 6) = (a - 2)(a - 8).

443. 1) 2a5b2 - 4a3b + 6a263 = 2a2b(a36 - 2a + 3b2);

2) mn3 + 5m2n2 - 7m2n = mn(n2 + 5mn - 7m);

3) xy2 + x2y - xy = xy(y + x - 1);

4) 9x3 + 4x2 - x = x(9x2 + 4x - 1);

5) -6m4 - 8m5 - 2m6 = -2m4(3 + 4m + m2);

6) 42a4b - 28a3b2 - 70a5b3 = 7a3b(6a - 4b - 10a2b2).

444. 1) m2n + mn + n = n(m2 + m + 1).

2) 3x6 + 6x5 - 15x4 = 3x4(x2 + 2x - 5);

3) 7a4b3 - 14a3b4 + 21a2b5 = 7a2b3(a2 - 2ab + 3b2);

4) 20b6c5 - 45b5c6 - 30b5c5 = 5b5c5(4b - 9c - 6).

445. 1) 4a + 4 = 4(a + 1);

2) 6аb - 3b = b(6a - 3);

3) -5x - 10y = -5(x + 2y);

4) x6 - x4 + x2 = x2(x4 - x2 + 1).

446. x + x2 = x(x + 1) — парне число, бо x і x + 1 — послідовні натуральні числа, тому їх добуток — парне число.

447. 1) a(2a + b)(a + b) - 4a(a + b)2 = a(a + b) • (2a + b - 4(a + b)) = a(a + b)(2a + b - 4a - 4b) = a(a + b)(-2a - 3b);

2) 3m2(m - 8) + 6m(m - 8)2 = 3m(m - 8) • (m + 2m - 16) = 3m(m - 8)(3m - 16);

3) (2а + 3)(а + 5) + (а - 1)(а + 5) = (а + 5) • (2а + 3 + а - 1) = (а + 5)(3а + 2);

4) (3х + 7)(4у - 1) - (4у - 1)(2х + 10) = (4у - 1)(3х + 7 - 2х - 10) = (4у - 1)(х - 3);

5) (5m - n)3(m + 8n)2 - (5m - n)2(m + 8n)3 = (5m - n)2(m + 8n)2(5m - n - m - 8n) = (5m - n)2(m + 8n)2(4m - 9n).

448. 1) (х - 6)(2х - 4) + (х - 6)(8 - х) = (х - 6)(2х - 4 + 8 - х) = (х - 6)(х + 4);

2) (х2 - 2)(3у + 5) - (х2 - 2)(у + 12) = (х2 - 2) • (3у + 5 - у - 12) = (х2 - 2)(2у - 7);

3) (4а - 3b)(5а + 8b) + (3b - 4а)(2а + b) = (4а - 3b)(5а + 8b - 2а - b) = (4а - 3b) • (3а + 7b);

4) (р - 9)4(2р + 1)3 + (р - 9)3(2р + 1)4 = (р - 9)3 • (2р + 1)3(р - 9 + 2р + 1) = (р - 9)3(2р + 1)3 • (3р - 8).